Electrophysiological and Morphological Properties of α and γ Motoneurons in the Rat Trigeminal Motor Nucleus - Nishimura, Kayo; Ohta, Masahiro; Saito, Mitsuru; Morita-Isogai, Yukako; Sato, Hajime; Kuramoto, Eriko; Yin, Dong Xu; Maeda, Yoshinobu; Kaneko, Takeshi; Yamashiro, Takashi; Takada, Kenji; Oh, Seog Bae; et al. (Frontiers in Cellular Neuroscience, 2018)
The muscle contraction during voluntary movement is regulated by activities of α- and γ-motoneurons (αMNs and γMNs, respectively). The tension of jaw-closing muscles can be finely tuned over a wide range. This excellent function is likely to be achieved by the specific populations of αMNs innervating jaw-closing muscles. Indeed, we have recently demonstrated that in the rat dorsolateral trigeminal motor nucleus (dl-TMN) the size distribution of αMNs was bimodal and the population of smaller αMNs showed a size distribution similar to that of γMNs, by immunohistochemically identifying αMNs and γMNs based on the expressions of estrogen-related receptor gamma (Err3) and neuronal DNA binding protein NeuN together with ChAT. This finding suggests the presence of αMNs as small as γMNs. However, differences in the electrophysiological membrane properties between αMNs and γMNs remain unknown also in the dl-TMN. Therefore, in the present study, we studied the electrophysiological membrane properties of MNs in the dl-TMN of infant rats at postnatal days 7–12 together with their morphological properties using whole-cell current-clamp recordings followed by immunohistochemical staining with an anti-NeuN and anti-ChAT antibodies. We found that the ChAT-positive and NeuN-positive αMNs were divided into two subclasses: the first one had a larger cell body and displayed a 4-aminopyridine (4-AP)-sensitive current while the second one had a smaller cell body and displayed a less prominent 4-AP-sensitive current and a low-threshold spike, suitable for their orderly recruitment. We finally found that γMNs showing ChAT-positive and NeuN-negative immunoreactivities had smaller cell bodies and displayed an afterdepolarization mediated by flufenamate-sensitive cation current. It is suggested that these electrophysiological and morphological features of MNs in the dl-TMN are well correlated with the precise control of occlusion.